Predictors of skills acquisition among students with learning disability in agricultural science subject - Abba, Umar Musa; Mat Rashid @ Mat Idris, Abdullah (Human Resource Management Academic Research Society, 2019)
In inclusive education principals’ competence, parent involvement and availability of infrastructure were viewed among the contributing factors that determines the effectiveness of secondary schools. Despite their important in the area, there was less substantial study regarding to these predictors in Adamawa state secondary schools. The aim of this study is to identify the predictor in the implementation of inclusive education on skills acquisition among students with learning disability in agricultural science subject. Therefore, the study investigated how the agricultural science teachers perceived the most predicting variable among the predictors in the implementation of inclusive education in Adamawa state secondary schools, Nigeria. The study employed a cross-sectional survey design with multi-stage cluster sampling technique. A validated survey instrument was distributed to 243 agriculture teachers in Nigeria that were asked about their perception on the selected factors in implementing inclusive education on skills acquisition among students with learning disability in agricultural science subject. The analysis of the data revealed that all the variables significantly predicted skill acquisition among students with learning disability in agricultural science subject, however; parent involvement appeared to be the leading predictor with (? = .397, P = .000). Therefore, in other to improve on the other predictors in Adamawa state secondary schools; it is essential to emanate an extensive, organized and rational program for improving their predicting effects by looking at the items that measured it in the questionnaire, thus may improve the level of effective implementation of inclusive education in Adamawa state secondary schools.